2017
DOI: 10.1515/eko-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Biological recovery the steppe of Hammada scoparia after enclosure in the region of Naama (Algeria)

Abstract: Boucherit H., Benabdeli K., Benaradj A.: Biological recovery the steppe of Hammada scoparia after enclosure in the region of Naama (Algeria). Ekológia (Bratislava), Vol. 36, No. 1, p. 52-59, 2017. This work was being carried out in the steppe of remth (Hammada scoparia) in Oranian part of the Saharan Atlas (Tiout -south of Naama). The H. scoparia of Saharan group occupies the foothills south of the Saharan Atlas and glazes and hamadas of the northern part of the Sahara where it seems to find its optimum dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It should be noted, however, that both management and land use have a profound effect on vegetation. Assessment of the enclosure of some steppes area in northern Algeria by Boucherit et al (2017) showed that grazing management could improve plant cover and diversity during the time. So in all studied stations, future management can improve vegetation conditions from cover and plant biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that both management and land use have a profound effect on vegetation. Assessment of the enclosure of some steppes area in northern Algeria by Boucherit et al (2017) showed that grazing management could improve plant cover and diversity during the time. So in all studied stations, future management can improve vegetation conditions from cover and plant biodiversity.…”
Section: Discussionmentioning
confidence: 99%